2023
DOI: 10.1007/s41810-023-00182-9
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Assessment of the Some Commercially Available Portable Bipolar Air Ionizers Particulate Pollutants (PM2.5, PM10) Removal Efficacies and Potential Byproduct Ozone Emission

Abstract: Indoor air cleaning interventions such as bipolar air ionizers have increased lately due to rampant air pollution and the COVID-19 pandemic. Hitherto, the bipolar air ionizer efficacy against particulate pollutants and byproduct ozone emission has not been fully understood and remained a critical concern. Currently, available diverse and complex methods are insufficient to determine commercially available bipolar air ionizer reliability. The National and International market of bipolar air ionizers is prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Albeit, there is no abnormal ozone emission observed in this study. Similarly, in our previous study, comparative results from several bipolar ionizers showed up to 80% particulate matter removal efficiency of tested bipolar air ionizers and negligible ozone (Gupta et al, 2023). Current and previous study data indicates ozone emission is not always linked with bipolar air ionizers air cleaning.…”
Section: Overall Particulate Matter Removal Efficacy Of Tested Baisupporting
confidence: 68%
See 2 more Smart Citations
“…Albeit, there is no abnormal ozone emission observed in this study. Similarly, in our previous study, comparative results from several bipolar ionizers showed up to 80% particulate matter removal efficiency of tested bipolar air ionizers and negligible ozone (Gupta et al, 2023). Current and previous study data indicates ozone emission is not always linked with bipolar air ionizers air cleaning.…”
Section: Overall Particulate Matter Removal Efficacy Of Tested Baisupporting
confidence: 68%
“…The air quality monitor is rechargeable and can transfer real-time data by Wireless Fidelity (WiFi) to the laboratory computer. The air quality monitor is customized with the required sensors (PM 2.5 , PM 10 , CO 2 , O 3 , Temp., RH) which have been employed in our previous study (Gupta et al, 2023) During experiments, ambient Particulate matter (PM) concentration in the study area was derived from the nearby regional air quality monitoring station (Knowledge Park-V, Greater Noida-UPPCB) operated by the central pollution control board of India (https://app.cpcbccr.com/AQI_India/).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation